Analisa Kepatuhan dalam Pemeriksaan Kesehatan Berkala untuk Mencegah Diabetes Mellitus Tipe 2 pada Usia Produktif di PKM Sukmajaya Tahun 2022: Analysis of Compliance in Periodic Health Checks to Prevent Type 2 Diabetes Mellitus in the Productive Age at PKM Sukmajaya in 2022 - Deliana, Sekar Okta; Sari, Emi Oktavia; Apriyanti, Hikmah; Pauziah, Syifa (MPI Press, 2023)
Background: One of the causes of diabetes mellitus is the community's non-compliance with regular health check-ups. Objective: To understand the compliance of the community in undergoing regular health check-ups to prevent type 2 diabetes mellitus at the Sukmajaya Community Health Center Unit (UPTD Puskesmas) in Depok City in 2022. Method: This research employs a descriptive analytic method with the population being the entire community in the Sukmajaya Community Health Center Unit area, Depok City, and a sample of 20 respondents. The research instrument used includes direct observation through interviews and the collection of secondary data from the monthly reports of the Sukmajaya Community Health Center Unit, the Health Profile of Depok City, and several journals from previous research. Data analysis is descriptive using the Criteria Matrix Technique. Results: Based on Sukmajaya Community Health Center Unit data for January-February, it was found that out of 701 patients who did not undergo regular health check-ups, 175 of them suffered from diabetes mellitus. Meanwhile, the research results show that 15 out of 20 respondents admitted to not regularly undergoing health check-ups. Conclusion: Factors contributing to non-compliance with health check-ups in the community are knowledge, perception, and economic factors, with knowledge being the dominant factor. Efforts that can be made include increasing public knowledge about the importance of regular health check-ups through health promotion based on digital media. Digital media in the form of a website can be an effective means to enhance public knowledge of health check-ups because it is easily accessible to anyone, anywhere.